1984
DOI: 10.1177/001789698404300402
|View full text |Cite
|
Sign up to set email alerts
|

Does tobacco sports sponsorship on television act as advertising to children?

Abstract: A REPRESENTATIVE survey of 880 children in first, third, and fifth years was carried out in five secondary schools in one education authority using an anonymous questionnaire. It was found that children were most aware of the cigarette brands which are most frequently associated with sponsored sporting events on TV. Children's TV viewing of a recent snooker championship sponsored by one cigarette manufacturer was positively correlated with the proportion of children associating that brand, and other brands use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 1 publication
2
34
0
Order By: Relevance
“…Most papers examining links between tobacco sponsorship and smoking have focused on young persons' brand awareness and recall, along with attitudes toward tobacco sponsorship of sport (e.g. Ledwith, 1984;Aitken, Leathar, & Squair, 1986;Hoek, Gendall, & Stockdale, 1993;McDaniel & Mason, 1999;Sparks, 1999). Ledwith (1984) conducted a notable study, finding a significant increase in cigarette brand awareness amongst 880 British secondary school students following a televised snooker competition sponsored by a cigarette manufacturer.…”
Section: Influences On Regulation Of Sport Sponsorshipmentioning
confidence: 99%
“…Most papers examining links between tobacco sponsorship and smoking have focused on young persons' brand awareness and recall, along with attitudes toward tobacco sponsorship of sport (e.g. Ledwith, 1984;Aitken, Leathar, & Squair, 1986;Hoek, Gendall, & Stockdale, 1993;McDaniel & Mason, 1999;Sparks, 1999). Ledwith (1984) conducted a notable study, finding a significant increase in cigarette brand awareness amongst 880 British secondary school students following a televised snooker competition sponsored by a cigarette manufacturer.…”
Section: Influences On Regulation Of Sport Sponsorshipmentioning
confidence: 99%
“…Aitken, Leathar, &S quair, 1986;Hoek, Gendall, &S tockdale, 1993;Ledwith, 1984;McDaniel &M ason, 1999;Sparks, 1999;Vaidya,Naik, &Vaidya,1996). However, regulatory restrictions on alcohol and fast food sponsorship are typicallyfar more lenient than on tobacco sponsorship because there is no 282 N. Hing et al…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are particularly alarming in light of the effect tobacco motor sports sponsorship has on youth smoking attitudes and behaviors [35][36][37][38][39][40][41][42][43] and the growing popularity of car racing among youths. 8,47,48 According to the Washington Post, "NASCAR is targeting young customers with everything from amusement parks to NASCAR Barbie, grooming its next generation of fans even as TV ratings and race-day attendance soar."…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] This research has found that cigarette sports sponsorship has profound effects on brand awareness, 35,36,[39][40][41] perceived connections between brands and sport, [35][36][37][38]40,42 associations between A B S T R A C T cigarette brands and excitement, 35 attitudes about smoking, 39,42,43 and smoking behavior. 41,42 Given the widespread television advertising exposure achieved by tobacco companies through sponsorship of motor sports, and given the evidence for an effect of this sponsorship on youth smoking attitudes and behavior, addressing tobacco motor sports sponsorship should be an important public health strategy.…”
Section: 4-8mentioning
confidence: 99%